2018
DOI: 10.1002/jaal.871
|View full text |Cite
|
Sign up to set email alerts
|

Writing Together: Online Synchronous Collaboration in Middle School

Abstract: The authors showcase the use of DocuViz, an information visualization tool, as a means to support middle school students’ online synchronous collaborative writing. The purpose of this study was to explore writing outcomes when students write in groups and independently. Providing students with a tool to help them understand their individual contributions to a collaboratively written Google Doc may be one reason why group‐written essays were significantly longer and received significantly higher rubric scores w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 19 publications
1
28
1
Order By: Relevance
“…This metacognitive skill, however, requires scaffolding during more dynamic forms of writing. Krishnan et al's (2018) study of a free tool, and Chrome add-on, for determining collaboration patterns in Google Docs (i.e., DocuViz) suggested that middle school students value this information when engaging in online SCW. DocuViz is a text-mining tool that produces a visual history chart of the emerging Google document across different timepoints.…”
Section: Feature Articlementioning
confidence: 99%
See 4 more Smart Citations
“…This metacognitive skill, however, requires scaffolding during more dynamic forms of writing. Krishnan et al's (2018) study of a free tool, and Chrome add-on, for determining collaboration patterns in Google Docs (i.e., DocuViz) suggested that middle school students value this information when engaging in online SCW. DocuViz is a text-mining tool that produces a visual history chart of the emerging Google document across different timepoints.…”
Section: Feature Articlementioning
confidence: 99%
“…Olson & Olson, 1996). In addition, online SCW that makes use of DocuViz supports students' later independent writing (Krishnan et al, 2018). Mr. Cusimano's students also reported that DocuViz encouraged them to write more and provided contribution transparency and accountability.…”
Section: Feature Articlementioning
confidence: 99%
See 3 more Smart Citations